Thermal Sensitivity of Heat Sensor TRPA1 Correlates With Temperatures Inducing Heat Avoidance Behavior in Terrestrial Ectotherms - Akashi, Hiroshi (Frontiers in Ecology and Evolution, 2021)
Temperature is an essential environmental factor that controls an organism’s performances. As ectothermic animals largely rely on external heat sources for adjusting their body temperature, thermal perception is a primary process of behavioral thermoregulation. Transient receptor potential ankyrin 1 (TRPA1) is a heat sensitive ion channel in most non-mammalian species, and its heat activation has been suggested to induce heat avoidance behaviors in ectothermic animals. However, associations between TRPA1 and ecologically relevant temperatures have not been investigated, and the analyses including diverse taxa will provide robust support for understanding the associations. Here, I conducted extensive literature review, and assembled published data on thermal threshold of TRPA1 and three physiological parameters: the experimental voluntary maximum (EVM), which is body temperatures when heat avoidance behaviors are induced; the critical thermal maximum (CTmax), which is a point in temperature beyond which an organism becomes incapacitated; and average body temperature (Tmean) recorded in the field. Then, I examined the relationships between thermal threshold of TRPA1 and each of the three physiological parameters. As phylogenetically closely related species tend to show similar trait values among species, I conducted the regression analyses by accounting for phylogenetic distances among species. This study supports previous research by affirming that thermal threshold of TRPA1 is substantially correlated with body temperature that the animals escaped from the heat source, represented here as EVM. Nevertheless, thermal threshold of TRPA1 showed a statistically insignificant correlation with CTmax and Tmean. The results suggest that although thermal threshold of TRPA1 is evolutionarily labile, its associations with EVM is highly conserved among diverse terrestrial ectotherms. Therefore, thermal threshold of TRPA1 could be a useful parameter to evaluate species vulnerability to thermal stress particularly in the recent climate warming scenario.